Peningkatan Kompetensi IT Guru Kelas di SD Negeri Induk Bangkinang Kota Dalam Pelaksanaan Kurikulum 2013 - Marwa, Safni; Dhora, Anna (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
In implementing the 2013 curriculum, competence and creative class teachers based IT (information technology) is essential. Not only is the use of the application reporting the results of students' studies, but also in the practice of teaching such as the use of computers and the Internet as a learning media. It's mostly class teachers, especially in the elementary school of the country in the Bangkinang Kota district, still not mastering and using the information technology. This led to a low level of basic schooling against both private primary schools carrying out the 2013 curriculum. For that, there needs to be an effort to improve class teacher competence at the primary school in the mastery of it in order to sustain the execution of the 2013 curriculum. As the elementary schools (SD Negeri) leader in the Bangkinang Kota, consists of three schools following: SD Negeri 003 Bangkinang Kota, SD Negeri 005 Langgini and SD Negeri 006 Langgini. Efforts to improve the competence of class teachers starting from evaluation, which is based on the evaluation will continued to the application usage and making media learning. As the end result, in classes and evaluation done enrichment capability it so teachers back against the more ready to the learning. Guiding primary the nucleus it needs to be done to giving effect to other public school Bangkinang Kota in particular